Framing Covid-19 vaccination: a study of Malaysian mainstream and alternative online news portals / Pui Gou Siang and Rani Ann Balaraman - Pui, Gou Siang; Balaraman, Rani Ann (Faculty of Communication and Media Studies (FCMS), 2022)
The COVID-19 pandemic is reaching a worrying state in Malaysia and the National COVID-19 Immunisation Programme has been initiated to tackle the pandemic. Various news pertaining to the COVID-19 vaccines have been reported and it raises questions of whether the way online news portals frame the news would influence the public's willingness to get vaccinated against COVID-19 or not. Building on previous literature examining the role of mass media in health communication and drawing on the theoretical concepts of framing, the study examined news stories published by New Straits Times Online, The Star Online, Malaysiakini, and Free Malaysia Today from March 1, 2021 to November 30, 2021.The findings concluded that there is a statistically significant difference in the use of news frames between the online news portals. The results obtained from the study may serve as a benchmark for journalists and media practitioners in their future reporting of vaccination news because they revealed the underlying news frames that influence one's understanding of core issues and problems revolving around the COVID-19 vaccination in Malaysia.